Aplikasi Metode Kendali LQR (Linier Quadratic Regulator) pada Sistem Suspensi Seperempat Mobil - Asfa'ani, Ezhari; Sari, Anisa Rizki; Hasibuan, Lilis Harianti (UIN Imam Bonjol Padang, 2024)
This research discusses the design of the Linear Quadratic Regulator (LQR) control method for car suspension systems. The car suspension systems considered are limited to quarter car models. The dynamic equations of the quarter car system are derived by applying Newton's Second Law. Next, a suspension system without control is compared with a suspension system that has been given control. The uncontrolled quarter car suspension system has an eigenvalue of -1.3658 + 0.0000i; 0.9635 + 0.0000i; -0.0488 + 0.3156i and -0.0488 - 0.3156i which means the system is unstable. Meanwhile, the quarter car suspension system that has been given LQR control has an eigenvalue of -111.8113; -74.4464; -36.9243 and -14.0242 which means the system is asymptotically stable. Based on eigenvalue analysis and numerical simulation, LQR control can stabilize the quarter car suspension system.